Trends and Problems of Information and Communications Technology (ICT) in Indonesia from the Perspective of Media Framing - Junaidi Junaidi (Jurnal Ilmu Komunikasi, 2016)
This research aims to study the way the media frame the trends and the problems of Information and Communications Technology (ICT) in Indonesia. This research uses Robert N Entman’s framing model to analyze ten headlines in ICT Magazine. The media see the development of ICT as a doubleedged sword, when it is not used wisely it would hurt its users. The development of ICT in Indonesia is characterized by certain interests and the influx of foreign workers having special qualifications which tend to bring disadvantage to the state. In addition, the government’s efforts to develop an internet-based economy gain great concern and positive framing from ICT Magazine.